Can citizen reporting apps plug the data gap in the Himalayan wildlife trade? - Harsh K. Chauhan (Elsevier, 2021)
The Himalayan region is particularly susceptible to biodiversity loss because it is ecologically rich, highly susceptible to climate change and natural hazards, and its governance is fragmented across multiple inter- and intra-national boundaries. Citizen reporting tools might provide an impetus for improving information-based management of wildlife trade that is lacking in the current regional political structure. Investment in citizen reporting tools could improve the availability of data on the status of existing species’ populations and trade of their commercial product. We outline how this recently-emerged tool is being used in the region and describe the challenges for and potential contribution of a citizen reporting app for combating illegal wildlife trade in the Himalayan region. Tweetable abstract: Citizen reporting tools could reduce biodiversity loss in the Himalayas by reducing illegal and destructive trade.